Effectiveness of the education program in the active learning strategies for students in the faculty of sciences of the education of the National University Hermilio Valdizán, Huánuco – 2012 - Rojas-Cotrina, Amancio R. (2019)
The present research had an objective: To determine the effectivenessthathasactive teaching program in learning strategies among students inthe Faculty ofEducation Sciences of theHermilioValdizán University, Huanuco - 2012.Towhichwe worked witha sample of 78students enrolled in the2nd grade of study, these students aredivided in two groups: Basic EducationandSecondary Education42 and36, the first was the control group and the secondexperimentalgroup. The researchdeveloped isApplied. The designthatwas appliedwas theTwoGroupsNotEquivalentorEquivalentControl Groupnot(or notRandomizedControlGroup). Was appliedto the experimental group the Active TeachingProgram. The results were: the learning strategiesbefore andafter the interventioninthe experimental groupwas compared withtheWilcoxontest, which is to compare thepositive and negativerangesofthe observed frequencies. 36rangesfoundpositive tonegative ranks0, which indicates astatisticallysignificant differenceofP ≤0.000. Therefore,it is assumed thatin the experimental groupafter the interventionofactive teaching program significantly increased scores onlearning strategies. Moreover,in the control groupwas foundpositive ranks18versus 14 negative ranksand10 draws which does not indicate astatisticallysignificant differencefinding aP ≤ 0.822. Therefore,it is assumed thatthe scoresremain constant with it demonstrated the effectiveness ofActiveLearning ProgramatLearningStrategies.